Відповідь:
Пояснення:
54 - 6 ( - 9+27x - 27) = 162 + 6
54 - 6 + 54 - 162x + 162 = 162 + 6
- 6 - 6 + 108 - 162x = 162 - 162
- 12 + 108 - 162x = 0
6x(- 2 + 18x - 27 ) = 0
D = 18*18 - 4*(-2)*(-27) = 324-216=108
= 6
x1 = 0
x2 = =
x3 = =
Объяснение:
54x²-6(x-3)³=162+6x³ |6
9x²-(x³-9x²+27x-27)=27+x³
9x²-x³+9x²-27x+27-27-x³=0
18x²-2x³-27x=0 |×(-1)
x(2x²-18x+27)=0
x₁=0
2x²-18x+27=0; D=324-216=108
x₂=(18-√(36·3))/4=(18-6√3)/4=(9-3√3)/2
x₃=(18+6√3)/4=(9+3√3)/2
ответ: 0; (9-3√3)/2; (9+√3)/2.
Відповідь:
Пояснення:
54 - 6 ( - 9+27x - 27) = 162 + 6
54 - 6 + 54 - 162x + 162 = 162 + 6
- 6 - 6 + 108 - 162x = 162 - 162
- 12 + 108 - 162x = 0
6x(- 2 + 18x - 27 ) = 0
D = 18*18 - 4*(-2)*(-27) = 324-216=108
= 6
x1 = 0
x2 = =
x3 = =
Объяснение:
54x²-6(x-3)³=162+6x³ |6
9x²-(x³-9x²+27x-27)=27+x³
9x²-x³+9x²-27x+27-27-x³=0
18x²-2x³-27x=0 |×(-1)
x(2x²-18x+27)=0
x₁=0
2x²-18x+27=0; D=324-216=108
x₂=(18-√(36·3))/4=(18-6√3)/4=(9-3√3)/2
x₃=(18+6√3)/4=(9+3√3)/2
ответ: 0; (9-3√3)/2; (9+√3)/2.